The effects of conservation agriculture under rain fed conditions in Chimanimani District - Karinda, Martin (BUSE, 2024)
The abstract of this research aims to provide a comprehensive analysis of the effects of conservation agriculture (CA) under rain-fed conditions in the Chimanimani District. This study investigates the impact of CA practices on soil health, crop yields, and socio-economic outcomes within the context of sustainable agriculture and agroecology theories. Utilizing both qualitative and quantitative research methodologies, the study employs thematic analysis to quantify the effects of CA while controlling for confounding variables. The research adheres to established protocols and standards in data collection and analysis as outlined by the Food and Agriculture Organization (FAO) and the Conservation Agriculture Network for Africa (CANA), ensuring methodological rigor and enhancing the reliability of the findings. Key assumptions include the willingness and ability of local farmers to adopt CA practices with adequate support, and the representativeness of the selected sample of respondents. Limitations such as the generalizability of findings to other regions and the logistical challenges posed by the rural setting are acknowledged. The study highlights the potential of CA to improve soil health, enhance crop productivity, and support sustainable farming practices, contributing valuable insights for policymakers, researchers, and local inhabitants in the field of climate change and sustainable development.
Keywords: Conservation Agriculture; Rain fed conditions; Chimanimani District